Pay satisfaction and work engagement among employees in private and national companies - Kulikowski, Konrad (Journal of Public Governance, 2016)
Work engagement and employee satisfaction are important predictors of work performance, absenteeism and health. However, little attention is still being paid to the engagement and satisfaction of employees of national companies. The aim of the paper is to answer the question of how the level of work engagement is represented by vigour and dedication, sati sfaction with pay and pay fairness among employees from national and private companies. An Internet-based opinion poll has been conducted in a group of 1065 employees of private companies and 203 employees of national companies, using the Utrecht Work Engagement Scale. It found that employees of national companies had significantly lower level of satisfaction with pay and pay fairness compared to employees of private companies. There also was a significant difference in the small effect size in the level of vigour, but no significant difference in the level of dedication between two groups could be observed. The results highlight low satisfaction with salaries of Polish employees of national companies, which may have a negative impact on the efficiency and quality of their work.